Emergence and dominance of CTX-M-15 extended spectrum beta-lactamase among Escherichia coli isolates from children - Réjiba, Samia (2011)
Of forty-seven extended-spectrum cephalosporin-resistant Escherichia coli isolates, collected from children at the Children’s Hospital in 2006 (Tunis, Tunisia), we analyzed 32 isolates that were genotypically different by enterobacterial repetitive intergenic consensus -polymerase chain reaction. For all isolates, the double-disk diffusion test revealed synergy between clavulanate and cefotaxime and/or ceftazidime, suggesting the production of extended-spectrum beta-lactamases. Polymerase chain reaction experiments, performed on plasmid DNA, and sequencing revealed the presence of blaTEM-1B (26 isolates, 81%), blaTEM-34(IRT-6) (3 isolates, 9%), blaSHV-12 (2 isolates, 6%), and blaCTX-M-15 (31 isolates, 97%). Further, the insertion sequence ISEcp1 was found upstream from the blaCTX-M-15 gene in 11 isolates. The bla genes were found alone or in various combinations in a single isolate. blaTEM-1B and blaCTX-M-15 genes were detected in 26 out of the 32 isolates. Three isolates harbored both blaTEM-34(IRT-6) and blaCTX-M-15. blaSHV-12 was identified either alone or with blaCTX-M-15 in a single isolate. Our investigation showed the dominance of CTX-M-type extended-spectrum beta-lactamases, with CTX-M-15 particularly common, and to our best knowledge, this is the first report of the coexistence of CTX-M-15 and IRT-6 in E. coli isolates from children in Tunisia.